DAMPAK PERUBAHAN POLA PEKERJAAN MASYARAKAT DI KAWASAN OBYEK WISATA ALAM NAGARI SILOKEK KECAMATAN SIJUNJUNG KABUPATEN SIJUNJUNG - ElpaFitri, Nora Refni (Pendidikan Sosiologi, 2014)
This thesis described the tour potential in nature tour area at Nagari Silokek can be a alternative of economy development through attraction program in the area. The research purposed to; (1) described goverment attempts in developing nature tour at Nagari Silokek, (2) described the effect of society economy from nature tour area at Silokek.In addition, this research used social changing theory. According to Peter Blau, there is two kinds of rewards, they are intrinsic and extrinsic. The approach of this research was qualitative research by conducting the descriptive study. It purposes to give the description about the problems which were analized. Then, the kinds of the data which researcher used were primer and sekunder data. Also, the informant of this research was taken by purposive technique sampling (the interview was done based on the particular criteria). In collecting data, the researcher used observation, interview and document study as method of collecting data. Then, the researcher analized the data by group the data. Then, it was analized by several steps; collection, reduction, present and draw the conclusion of data.As the finding of this research were divided into goverment attempts in developing nature tour places in Silokek, Sijunjung District, Sijunjung regency and the effect of model of society job at the tour place, Silokek. First, goverment attempts in developing nature tour area in Silokek were 1) recontructing the street about 15Km to Silokek and area of tour object, Silokek, 2) building the accomodation such as Mosque, landscape, toilet, promotion shops and buying tour ship and 3) promotion of tourism. Second, the effect of pattern of society job in Silokek such as 1) open the chance of the society to work in the tour area, 2) increase the income of seller and 3) contruct the tour organization in Silokek.